OPTIMIZING THE ROLE OF GUIDANCE AND COUNSELING TEACHERS IN THE COVID-19 PANDEMIC - Yayuk Primawati; Yuyun Yunita (Insititut Agama Islam Agus Salim Metro Lampung, 2021)
Guidance and Counseling teachers are professional educators with minimum academic qualifications of Bachelor of Education (S-1) in the field of Guidance and Counseling and have competence in the field of Guidance and Counseling with the task of carrying out guidance and counseling services, namely educating , guiding, and developing the abilities of students in solve problems experienced and all their potential through guidance and counseling services. A counselor must have good actualization in his field so that the services provided are truly part of the counselor's full work to his students. It is intended that students can achieve their competence according to the period of development. In this case the counseling teacher needsto provide various assistance services according to the needs of students so that they can act and behave in accordance with the demands and conditions of the school environment, family and community to achieve optimal development. Since the implementation of distance learning at home through the network (online), Counseling Guidance (BK) teachers often get less attention. In general, schools and teachers focus on providing material to students, while in its implementation, many problems faced by students demand the presence of BK teachers. BK teachers need to be involved in the online learning process because understanding of the BK disciplines is intended for solving problems that are often faced by students. The role of the guidance counseling teacher is very much needed in online learning today.